Features of application of raltegravir in HIV-infected patients with different somatic pathologies - N. V. Sizova; E. S. Obizhaeva; S. O. Mayorova (Журнал инфектологии, 2021)
Purpose of the study. Evaluation of the efficacy, safety and tolerability of raltegravir regimens in HIV-infected patients with concomitant pathology in real clinical practice.Materials and methods. A retrospective analysis was carried out of 277 outpatient records of HIV-infected patients who received raltegravir (RAL) as a third component both in patients without previous experience of antiretroviral therapy (ART) and in patients with experience of treatment with various somatic pathologies. The main criterion for the effectiveness of the scheme was the proportion of patients with undetectable viral load at the start of the analysis. Additional criteria for evaluating the efficacy and safety of the regimen were the dynamics of the number of CD4-lymphocytes, the frequency and nature of undesirable side reactions.Results. On average, patients with no experience of treatment and with experience of treatment received regimens with raltegravir for about 5 years. At the time of the study in 2020, 69.8% of patients on ART for the first time continued to take a regimen containing raltegravir. In this group, the proportion of patients with virological suppression (PCR of HIV RNA less than 50 kopecks / ml) was 97.7%. 75.2% of patients in the second group in 2020 continued to take the RAL regimen. The proportion of patients with virological suppression (VL less than 50 kopecks / ml) in this group was 97.5%. During the treatment, there was no discontinuation of the regimen in both groups due to undesirable side reactions to raltegravir.Conclusion. The results of this study confirm that RAL-based regimens provide a high level of efficacy with a good tolerance and safety profile in routine clinical practice for both naive and experienced patients with various somatic pathologies.